2017
DOI: 10.1097/qad.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

HIV persists in CCR6+CD4+ T cells from colon and blood during antiretroviral therapy

Abstract: Objectives To investigate the contribution of colon and blood CD4+ T-cell subsets expressing the chemokine receptor CCR6 to HIV persistence during ART. Design Matched sigmoid biopsies and blood samples (n=13) as well as leukapheresis (n=20) were collected from chronically HIV-infected individuals receiving ART. Subsets of CD4+ T-cells with distinct differentiation/polarization profiles were identified using surface markers as follows: memory (TM, CD45RA-), central memory (TCM; CD45RA−CCR7+), effector (TEM/TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
185
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(197 citation statements)
references
References 102 publications
12
185
0
Order By: Relevance
“…Of particular importance, Li et al recently demonstrated that acitretin, a RA derivative, increases HIV transcription in CD4 + T cells from ART-treated HIV-infected individuals and enhances RIG-I signaling, thus leading to an antiviral response and the apoptosis of infected cells (68). Similarly, in a previous report (37) and in this manuscript, we demonstrated that ATRA significantly increases HIV reactivation in a VOA without significant changes observed in T cell survival/proliferation. Differences between our results and those published by Li et al (68) may be explained by differences in the experimental design.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Of particular importance, Li et al recently demonstrated that acitretin, a RA derivative, increases HIV transcription in CD4 + T cells from ART-treated HIV-infected individuals and enhances RIG-I signaling, thus leading to an antiviral response and the apoptosis of infected cells (68). Similarly, in a previous report (37) and in this manuscript, we demonstrated that ATRA significantly increases HIV reactivation in a VOA without significant changes observed in T cell survival/proliferation. Differences between our results and those published by Li et al (68) may be explained by differences in the experimental design.…”
Section: Discussionsupporting
confidence: 83%
“…Of particular importance, we found that CCR6 + cells but not CCR6 -T cells infiltrating the colons of HIV-infected individuals receiving ART express a unique molecular signature, including superior levels of CCR5, integrin β7, and phosphorylated mTOR expression, likely as a consequence of ATRA exposure in the intestinal environment (12,41). In line with our recent report that HIV DNA persists in colon-infiltrating CCR6 + T cells during ART (37), it remains to be determined whether mTOR expression identifies a fraction of CCR6 + T cells enriched in HIV DNA and whether mTOR activation contributes to residual HIV replication in colon-infiltrating CCR6 + T cells during ART. While this manuscript was in preparation for submission, Besnard et al reported the results of a shR-NA screen that revealed mTOR as a regulator of HIV latency (86) via mechanisms involving CDK9 and NF-κB activation that controls Tat-dependent HIV transcription (86).…”
Section: On Hiv Replication In Ccr6supporting
confidence: 86%
See 3 more Smart Citations